Devaluation and Pricing Decisions : a case study approach - Hague, D. C. (Douglas Chalmers), 1926-2015.; Oakeshott, W. E. F. (W. Evelyn F.); Strain, A. A. (Adrian Anthony); Manchester Business School. Centre for Business Research (New York: Routledge, 2022)
First published in 1974, Devaluation and Pricing Decisions is based on case studies of the export pricing decisions made by nineteen major British companies after the 1967 devaluation. The aim was to look in detail at the decisions that major British firms took after devaluation and to see how they had responded to this major change in government policy. This book shows how far the firms had anticipated the devaluation; what company objectives were at that time and what changes in these objectives, or in pricing and marketing policies, were made to take advantage of new opportunities for exporting and for import substitution. The researchers also examined the actual process of decision making to find what information was available to the decision makers and how they used it. The book is directed to businessmen taking decisions on export prices and marketing in the world of today where foreign exchange rates change frequently. It is also directed towards those responsible for shaping national economic policy. For students of economics, it represents a study showing, in considerable detail, how a number of businesses responded to the 1967 devaluation.
Keywords: Devaluation of currency -- Great Britain; Pricing -- Great Britain; Devaluation of currency; Pricing; Great Britain